A pheromone lure for catching fall armyworm males (Lepidoptera: Noctuidae) in Mexico - Cruz-Esteban, Samuel; Rojas, Julio Cesar; Malo, Edi Alvaro (Instituto de Ecología, A.C., 2020)
Moth sex pheromones can be used for monitoring or for control (e.g., mass trapping or mating disruption) of agricultural pests. However, pheromone application in field conditions requires that all crucial pheromonal components are included and optimized in a pheromone lure. In this study, we optimized a sex pheromone lure for monitoring Mexican populations from the fall armyworm (FAW), Spodoptera frugiperda Smith. In corn fields, we evaluated the activity of single compounds, three binary blends, and one tertiary blend of (Z)-7-dodecenyl acetate (Z7-12:OAc), (Z)-9-tetradecenyl acetate (Z9-14:OAc), and (Z)-11-hexadecenyl acetate (Z11-16:OAc). The results showed that the traps baited with a binary blend of Z7-12:Ac + Z9-14:Ac captured significantly more S. frugiperda males than single compounds, other binary blends or the tertiary blend. The absence of Z11-16:OAc in the blends did not significantly affect the capture of males, indicating that this compound is non-essential for male attraction in the field. We demonstrated that the dose of the binary blend of Z7-12:OAc and Z9-14:OAc influenced the catch rate of FAW males. The pheromone lure optimized in this study can be useful for capturing S. frugiperda in Mexico.